Diversity and conservation status of palms (Arecaceae) in two hotspots of biodiversity in Colombia and Ecuador - Thomas L. P. Couvreur; Nayeli Jijon; Rommel Montúfar; Paula A. Morales‐Morales; Maria José Sanín; Juan Carlos Copete; Alix Lozinguez; Álvaro J. Pérez; Emily Beech (Plants, People, Planet, 2024)
Societal Impact Statement Palms provide vital plant resources and ecosystem services to people across the tropics. To improve conservation guidance, a “health check” of palms in two highly threatened biodiversity hotspots in Colombia and Ecuador was undertaken. Palms are very diverse in these regions, but over one third are threatened with extinction now, especially among endemic species. Widespread and useful palms are also under intense human pressure and need to be prioritized in terms of sustainable management practices. Given the importance of palms for humans, inclusive conservation actions should be continued in both countries in order to safeguard this resource. Summary Palms provide central plant resources to societies in the tropics, especially in the Global South. The western Pacific and Andean regions of Colombia and Ecuador host two hotspots of biodiversity. To prioritize conservation policies towards palms, we undertook a conservation assessment of species in the region. We compiled a taxonomically verified database of specimens collected in both hotspots. We inferred preliminary conservation assessments using International Union for Conservation of Nature (IUCN) Criteria B. In addition, we evaluated the level of exposure of palms to human use and population density using the anthrome concept. We documented 144 native palm species in 33 genera occurring in both hotspots of Colombia and Ecuador. Of these, 55 are endemic to this region. We recorded 133 species for Colombia, 43 endemic, and 71 species for Ecuador, 9 endemic. A third of all palm species in the region are potentially threatened with extinction (50/144) and 12 as preliminary Critically Endangered. Aiphanes and Geonoma have the highest number of threatened species. In total, 60% of palm specimens were collected in the “low human impact” anthrome type. In contrast, 41% of specimens occur in high human density areas. The two hotspots of biodiversity in Colombia and Ecuador are very diverse in palms. However, we show that this diversity is under threat and is predominantly found in areas impacted by human activities. Extinction risk is highest in endemic species in both countries. Widespread and useful palm species also face threats linked to overexploitation or habitat loss. Inclusive conservation measures should be designed to conserve, together with communities, this plant resource.